Why Is It So Hard to Finance Budget Deficits? : Problems of a Developing Country - Iwata, Shigeru (IMF Working Papers; Working Paper, 2002)
This paper examines possible ways for a developing country to finance budget deficits from domestic resources. It does so by analyzing Pakistan's National Savings Scheme (NSS). The NSS has a number of unusual attributes, and its impact upon the economy of Pakistan is not clear, but given Pakistan's chronic fiscal difficulties, the NSS is of great importance in financing the public sector deficit. We use an econometric model to analyze the relationship between the demands for NSS deposits and various other financial instruments, in particular, bank deposits, and foreign-currency deposits. We conclude that NSS and bank deposits are net substitutes, as are NSS and foreign-currency deposits. Bank deposits and foreign-currency deposits, however, seem to be neither substitutes nor complements. Also, the estimated income elasticity of the demand for bank deposits is negative, while that of foreign-currency deposits is positive, and that of NSS is not significantly different from zero. Finally, there is evidence that foreign-currency deposits are a net substitute for NSS deposits. Thus, there is some empirical evidence that foreign currency deposits have absorbed part of the demand for NSS deposits. Accordingly, the availability of foreign-currency deposits may have reduced the ability of the government to finance itself.